КОНЦЕПТ «УТОПІЇ» ПОЛЯ РІКЕРА: СПРОБА АКТУАЛЬНОЇ РЕЦЕПЦІЇ ВАЖЛИВИХ ПОНЯТЬ - ПАРАЩИЧ, ВІТАЛІЙ (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
У статі робиться спроба реконструкції механізмів рецепції концепту «утопії» способом максимально можливої локалізації значення. На прикладі дескриптивного розбору цього поняття у праці П. Рікера «Ідеологія та утопія» – актуалізованого появою його українського перекладу – обґрунтовується важливість освоєння такого досвіду для економіки тривання суб’єкту у місці «тут». Паращич В. КОНЦЕПТ «УТОПИИ» ПОЛЯ РИКЕРА: ПОПЫТКА АКТУАЛЬНОЙ РЕЦЕПЦИИ ВАЖНЫХ ПОНЯТИЙ В статье предпринята попытка реконструкции механизмов рецепции концепта «утопия» с помощью максимально возможной локализации значений. На примере дескриптивного разбора этого понятия в роботе П. Рикера «Идеология и утопия» – актуализированного выходом его украинского перевода – обосновывается важность освоения такого опыта для экономики существования субъекта в месте «тут». Ключевые слова: утопия; локальность; П. Рикер; реконструкция опыта; рецепция. Paraschich V. THE CONCEPT «UTOPIA» BY PAUL RICEUR: A SAMPLE OF THE ACTUAL RECEPTION OF IMPORTANT CONCEPTS In this chapter the author has made an attempt of reconstructing mechanisms of the concept «Utopia» reception by means of the most possible localization of meanings based on the example of the descriptive analysis of this concept. Paul Riceur in his work «Lectures on Ideology and Utopia», actualized by its Ukrainian translation, substantiates the importance of assimilating such an experience for economy of a subject existence in this part and here. Key words: Utopia; local; Paul Riceur; experience reconstruction; reception